Evaluation of a custom single Peltier-cooled ablation cell for elemental imaging of biological samples in laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). Issue 4 (25th January 2016) - Hamilton, J. S.; Gorishek, E. L.; Mach, P. M.; Sturtevant, D.; Ladage, M. L.; Suzuki, N.; Padilla, P. A.; Mittler, R.; Chapman, K. D.; Verbeck, G. F.
Abstract : A new single Peltier element ablation cell is described and its applicability to biological sampling discussed to evaluate its performance. Abstract : The advent of laser ablation coupled to inductively coupled plasma-mass spectrometry has allowed for the elemental analysis of solid samples in their native state, or with little sample preparation required. Furthermore, with the addition of a cooled ablation cell spatially resolved elemental imaging of soft and semi-soft samples, specifically biological tissues, is attainable. A new single Peltier element laser ablation cell is described and a demonstration of its applicability to biological sampling is discussed to evaluate its performance. Through the analysis of three different biological tissues the device is shown to provide spatially resolved images of mapped elements while maintaining the structural integrity of the tissues during the hours long sampling times.